Sonographically guided, transcatheter foam sclerotherapy of the great saphenous vein - Hahn, M.; Schulz, T.; Jünger, M. (Phlebologie, 2007)
Objective: The goal of the study was to assess the effectiveness and patient tolerability of single-session, sonographically guided, transcatheter foam sclerotherapy and to evaluate its economic impact. Patients, methods: We treated 20 patients with a total of 22 varicoses of the great saphenous vein (GSV) in Hach stage III-IV, clinical stage C2-C5 and a mean GSV diameter of 9 mm (range: 7 to 13 mm). We used 10 ml 3% Aethoxysklerol®. Additional varicoses of the auxiliary veins of the GSV were sclerosed immediately afterwards. Results: The occlusion rate in the treated GSVs was 100% one week after therapy as demonstrated with duplex sonography. The cost of the procedure was 207.91 E including follow-up visit, with an average loss of working time of 0.6 days. After one year one patient showed clinical signs of recurrent varicosis in the GSV; duplex sonography showed reflux in the region of the saphenofemoral junction in a total of seven patients (32% of the treated GSVs). Conclusion: Transcatheter foam sclerotherapy of the GSV is a cost-effective, safe method of treating varicoses of GSV and broadens the spectrum of therapeutic options. Relapses can be re-treated inexpensively with sclerotherapy.
Keywords: Foam sclerotherapy; endoluminal therapy; insufficiency of the deep veins; healthcare oeconomics